Continental Philosophy of Technoscience - Zwart, Hub (Philosophy of Engineering and Technology, 2022)
The key objective of this volume is to allow philosophy students and early-stage researchers to become practicing philosophers in technoscientific settings. Zwart focuses on the methodological issue of how to practice continental philosophy of technoscience today. This text draws upon continental authors such as Hegel, Engels, Heidegger, Bachelard and Lacan (and their fields of dialectics, phenomenology and psychoanalysis) in developing a coherent message around the technicity of science or rather, "technoscience". Within technoscience, the focus will be on recent developments in life sciences research, such as genomics, post-genomics, synthetic biology and global ecology. This book uniquely presents continental perspectives that tend to be underrepresented in mainstream philosophy of science, yet entail crucial insights for coming to terms with technoscience as it is evolving on a global scale today. This is an open access book.